First symmetry tests in polarized Z0 decays to bbg. - Abe, K; Abe, K; Abe, T; Adam, I; Akimoto, H; Aston, D; Baird, K; Baltay, C; Band, H; Barklow, T; Bauer, J; Bellodi, G; et al. (2001)
We have made the first direct symmetry tests in the decays of polarized Z0 bosons into fully identified bbg states, collected in the SLD experiment at SLAC. We searched for evidence of parity violation at the bbg vertex by studying the asymmetries in the b-quark polar- and azimuthal-angle distributions, and for evidence of T-odd, CP-even or CP-odd, final-state interactions by measuring angular correlations between the three-jet plane and the Z0 polarization. We found results consistent with standard model expectations and set 95% C. limits on anomalous contributions.